2015
DOI: 10.1080/07373937.2015.1072548
|View full text |Cite
|
Sign up to set email alerts
|

Changes of oxygen-containing groups during thermal treatment and their influences on moisture readsorption of lignite

Abstract: The changes of oxygen-containing groups in the thermal treatment process of lignite were analysed and the moisture re-adsorption amounts of upgraded coals were related in this study. Chemical titration method was applied to determine the types and contents of oxygen-containing groups in raw lignite and upgraded coals obtained in the temperature range of 353-633K and under atmospheres of argon, air and carbon dioxide respectively.Experimental results showed that the oxygen-containing groups mainly involved carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The content of phenolic hydroxyl group was obtained in accordance with the difference in the values of the total acid (summation of phenolic and carboxylic acids) and carboxylic acid contents. The content of total acid (summation of phenolic and carboxylic acids) could be determined by the method mentioned above, which could be found in our previous study …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The content of phenolic hydroxyl group was obtained in accordance with the difference in the values of the total acid (summation of phenolic and carboxylic acids) and carboxylic acid contents. The content of total acid (summation of phenolic and carboxylic acids) could be determined by the method mentioned above, which could be found in our previous study …”
Section: Methodsmentioning
confidence: 99%
“…The content of total acid (summation of phenolic and carboxylic acids) could be determined by the method mentioned above, which could be found in our previous study. 16 The static N 2 adsorption instrument (JW-BK122W) was carried out to measure the specific surface area and the pore volume of the coal samples. About 1.5 g coal sample was weighted into a sample tube to be degassed at 70 °C for 24 h for all samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi and his coworkers investigated moisture re-adsorption behavior of upgraded low rank coal produced by a coal-oil slurry dewatering process [19] . The moisture re-adsorption behavior of coal samples dried at different temperatures was studied, and Jing found that the equilibrium moisture content decreased with increasing of drying temperature [20] .…”
Section: Introductionmentioning
confidence: 99%